2021
DOI: 10.3389/fendo.2021.630832
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for Live Birth in Fresh In Vitro Fertilization/Intracytoplasmic Sperm Injection Treatment in Poor Ovarian Reserve Patients Classified by the POSEIDON Criteria

Abstract: The mechanisms underlying poor ovarian response (POR) in assisted reproductive technology remain unclear, there is no consensus on the management of poor responders, the POSEIDON stratification classifies infertility patients into “expected” or “unexpected” groups to provide a more nuanced picture of POR, but few researchers have discussed the independent predictive factors (smoothed plots and the threshold effect) for live birth in POR patients classified by the new criteria. We conducted a retrospective coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…To better manage POR patients, the 2016 POSEIDON criteria classified POR patients into POSEIDON groups 1 and 2 due to abnormal ovarian response to exogenous gonadotropin and POSEIDON groups 3 and 4 due to decreased ovarian reserve based on age and the ovarian reserve parameters AFC and AMH, which improved the homogeneity and comparability of clinical studies and was conducive to providing more accurate assisted pregnancy strategies for POR patients ( 10 , 25 ). Female age, BMI, AFC, and COH protocols were independent predictors of live birth in POR patients according to the POSEIDON criteria ( 26 , 27 ). The previous retrospective analysis on the impact of BMI on the pregnancy outcome of FET showed that low BMI had no significant impact on the live birth rate, while obesity was closely associated with decreased clinical pregnancy rate and live birth rate ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 97%
“…To better manage POR patients, the 2016 POSEIDON criteria classified POR patients into POSEIDON groups 1 and 2 due to abnormal ovarian response to exogenous gonadotropin and POSEIDON groups 3 and 4 due to decreased ovarian reserve based on age and the ovarian reserve parameters AFC and AMH, which improved the homogeneity and comparability of clinical studies and was conducive to providing more accurate assisted pregnancy strategies for POR patients ( 10 , 25 ). Female age, BMI, AFC, and COH protocols were independent predictors of live birth in POR patients according to the POSEIDON criteria ( 26 , 27 ). The previous retrospective analysis on the impact of BMI on the pregnancy outcome of FET showed that low BMI had no significant impact on the live birth rate, while obesity was closely associated with decreased clinical pregnancy rate and live birth rate ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 97%
“…In a clinical pregnancy failure prediction model based on 281 POR patients, is still conducted according to the Bologna criteria, cannot be distinguished the biological heterogeneity of patients with POR (18,19). Another study found independent predictors of live birth in POR patients based on the POSEIDON criteria, but failed to develop a complete live birth predictive model (20). Conforti et al found that, with the increasing age of the first delivery in recent years, the proportion of patients in group 4 under POSEIDON criteria is as high as 55%, and the proportion of patients in group 3 is about 10% (21).…”
Section: Discussionmentioning
confidence: 99%
“…In a clinical pregnancy failure prediction model based on 281 POR patients, is still conducted according to the Bologna criteria, cannot be distinguished the biological heterogeneity of patients with POR ( 18 , 19 ). Another study found independent predictors of live birth in POR patients based on the POSEIDON criteria, but failed to develop a complete live birth predictive model ( 20 ). Conforti et al.…”
Section: Discussionmentioning
confidence: 99%